A Systematic Review of Effect of Prenatal Zinc Supplementation on Birthweight: Meta-analysis of 17 Randomized Controlled Trials - Gebraselassie, Samson G; Gashe, Fikre E (Journal of Health, Population and Nutrition, 2011)
The effect of prenatal zinc supplementation on birthweight is controversial as randomized controlled trials (RCTs) report conflicting conclusions. A systematic review which includes meta-analysis was done on 17 RCTs conducted worldwide since 1984 to assess the effect of prenatal zinc supplementation on birthweight. The studies were identified through web-based search. Heterogeneity among studies was assessed using Cochrane Q test statistic. Effect-size was measured based on standardized mean difference. Pooled effect-size was computed using a variant of random effect model. Thirteen of the 17 RCTs found no association, three reported positive association, and one reported negative association. Based on fixed and random effect models, the pooled effect-sizes were 0.0268 [95% confidence interval (CI) 0.0764, -0.0229) and 0.0712 (95% CI 0.1619, -0.0194) respectively. The effect-size estimate remains insignificant after stratification was made based on the dose of supplementation (optimal vs high dose), type of study (community vs institution- based), and type of source country (developed vs developing). The meta-analysis did not witness any association between birthweight and prenatal zinc supplementation. Key words: Birthweight; Medical research; Meta-analysis; Impact studies; Randomized control trails; Systematic review; Zinc supplementation DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7855 J HEALTH POPUL NUTR 2011 Apr;29(2):134-140